Evolution of Energetic Proton Parallel Pressure Anisotropy at Geosynchronous Altitudes: Potential Role in Triggering Substorm Expansion Phase Onset - S. S. Babu; I. R. Mann; S. Dimitrakoudis; L. G. Ozeke; I. J. Rae; C. Forsyth; A. W. Smith (Geophysical Research Letters)
Abstract The sequence of events associated with the triggering of energy release during substorm expansion phase onset is still not well‐understood. Oberhagemann and Mann (2020b, https://doi.org/10.1029/2019gl085271) proposed a new substorm onset mechanism, where the transition toward parallel proton pressure anisotropy during tail stretching in the late growth phase could trigger a pressure anisotropic ballooning instability. Here we examine the evolution of energetic proton parallel pressure anisotropy at geosynchronous altitudes, seeking evidence in support of the proposed substorm onset mechanism. We use the Geostationary Operational Environment Satellite (GOES) proton flux and magnetometer data combined with substorm onset indicators derived from ground‐based magnetometers. Superposed epoch analysis of substorm onset times for 2014 using the isolated substorm list (Ohtani & Gjerloev, 2020, https://doi.org/10.1029/2020ja027902) clearly shows signatures of energetic proton parallel pressure anisotropy immediately before substorm onset, potentially supportive of the Oberhagemann and Mann theory.